Avaliação da eficácia de programa de capacitação parental universal (ACT) pelo uso da observação - Pontes, Luciana Barbalho (2015)
This thesis involves a compilation of two manuscripts, presenting a systematic review of evaluation studies involving the ACT Raising Safe Kids Program and a pilot study evaluating the ACT Program in Brazil. Such program consists of a universal parenting prevention program that has reached several parents across the world since 2001. From the literature review, the absence of observational measures was a recurrent limitation mentioned in the evaluation studies of the program, with data exclusively based on self-reports. Faced with this gap, a pilot evaluation study of the ACT program involving observational measures of caregiver-child interaction before, after and three months after the intervention was developed, to assess the effects of the intervention on the program participants, along with self-report instruments. As a result, the participants in the Experimental Group had a significant increase in problem-solving skills after program completion. As one of the first studies to evaluate the ACT Program in Brazil, the study demonstrates the applicability of the program in the country, suggesting further studies to evaluate the effectiveness of the program in Brazil and contribute to the reinforcement of the scientific bases of the program.